Kesejahteraan subjektif ibu bapa kanak-kanak kurang upaya pembelajaran : pengaruh komitmen keagamaan, harapan terhadap anak, dan sokongan sosial - Calistina Ubeh; Ferlis Bahari; Peter Voo Su Kiong (Penerbit Universiti Kebangsaan Malaysia, 2017)
Past studies about parents raising children with disabilities have provided evidence that vary in terms of mental health, which eventually promotes further research focusing particularly on positive aspects such as subjective well-being. Based on positive psychology orientation, this study aims to identify the effects of religious commitment, hope for child, and social support on subjective well-being. A Quanti tative study using questionnaire was conducted on a total of 328 parents of children with learning disabilities. The instruments used including Religious Commitment Inventory-10, Parents' Hope for Their Child Scale, Multidimensional Scale of Perceived Social Support, Satisfaction with Life Scale, and the Positive and Negative Affect Schedule. The data were then analyzed using Partial Least Squre Structural Equation Modeling (PLS-SEM). Overall, the results showed Hope for child and social support significantly influence parent’s subjective well-being, whereas religious commitment only shows a significant effect on positive affect dimension. It can be concluded that religious commitment, hope for child, and social support as a potential predictor which enhance parent’s subjective well-being. More effort and systematic study are needed to understand and assist better parents of children with learning disabilities.